Autobiographical memory as a latent vulnerability mechanism following childhood maltreatment: Association with future depression symptoms and prosocial behavior. (October 2021) - Puetz, Vanessa B.; Viding, Essi; Hoffmann, Ferdinand; Gerin, Mattia I.; Sharp, Molly; Rankin, Georgia; Maguire, Eleanor A.; Mechelli, Andrea; McCrory, Eamon J.
Abstract: Objectives: Childhood maltreatment is associated with altered neural reactivity during autobiographical memory (ABM) recall and a pattern of overgeneral memory (OGM). Altered ABM and OGM have been linked with psychopathology and poorer social functioning. The present study investigated the association between altered ABM and subsequent socio-emotional functioning (measured two years later) in a sample of adolescents with ( N = 20; maltreatment group, MT) and without ( N = 17; non-MT group) documented childhood maltreatment histories. Method: At baseline, adolescents (aged 12.6 ± 1.45 years) were administered the Autobiographical Memory Test to measure OGM. Participants also recalled specific ABMs in response to emotionally valenced cue words during functional MRI. Adolescents in both groups underwent assessments measuring depressive symptoms and prosocial behavior at both timepoints. Regression analyses were carried out to predict outcome measures at follow-up controlling for baseline levels. Results: In the MT group, greater OGM at baseline significantly predicted reduced prosocial behavior at follow-up and showed a trend level association with elevated depressive symptoms. Patterns of altered ABM-related brain activity did not significantly predict future psycho-social functioning. Conclusions: The current findings highlight the potential value of OGM as a cognitive mechanism that could be targeted to reduce risk of depression in adolescents with prior histories of maltreatment.